Characterization of lactic acid bacteria from buffalo dairy product (dadiah) as potential probiotics (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Aritonang SN, Roza E, Yetmaneli, Sandra A, Rizqan. 2022. Characterization of Lactic Acid Bacteria from Buffalo Dairy Product (Dadiah) as Potential Probiotics. Biodiversitas 23: 4418-4423. Dadiah is one of fermented milk from West Sumatra which made from buffalo milk. These product made traditionally by pouring fresh buffalo milk into a bamboo stick covered with banana leaves and fermenting at room temperature for two days. The study's objective was to isolate and identify Lactic Acid Bacteria (LAB) from dadiah as candidates for probiotics. The factors that are considered are LAB Characterization, Biochemical and Microscopic Characterization of LAB Isolate, Bacterial Resistance in Acidic conditions, Bile Salts Resistance, and Antimicrobial Activity. Furthermore the isolate identify by Polymerase Chain Reaction (PCR) using 16S rRNA. Samples of dadiah were collected from five farmers in Tanjung Bonai Village, North Lintau Buo Regency, Tanah Datar District, West Sumatra, Indonesia. Observations were made in four replications, and the data obtained were analyzed descriptively. The total colony of lactic acid bacteria from dadiah was 7x108-23x108 CFU/mL. LAB isolates from dadiah were classified as Gram-positive bacilli. The isolates are resistant to acidic conditions and bile salts and have inhibitory activity against pathogenic bacteria. Identifying the selected isolate using the 16S rRNA showed that the isolate had similarities with Lactobacillus casei strain HDS-01. It can be concluded that dadiah used in this study is as a probiotic food.
Keywords: 16S rRNA, Dadih, LAB, Lactobacillus casei strain HDS-01, probiotics